2018
DOI: 10.1021/acs.bioconjchem.8b00760
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Additives Significantly Enhance Glycopolymer-Mediated Transfection of Large Plasmids and Functional CRISPR-Cas9 Transcription Activation Ex Vivo in Primary Human Fibroblasts and Induced Pluripotent Stem Cells

Abstract: Fast, efficient, and inexpensive methods for delivering functional nucleic acids to primary human cell types are needed to advance regenerative medicine and cell therapies. Plasmid-based gene editing (such as with CRISPR-Cas9) can require the delivery of plasmids that are large (∼9.5–13 kbp) in comparison to common reporter plasmids (∼5–8 kbp). To develop more efficient plasmid delivery vehicles, we investigated the effect of plasmid size on the transfection of primary human dermal fibroblasts (HDFs) and induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 59 publications
0
27
0
2
Order By: Relevance
“…299 Dexamethasone dilates the nuclear pores, which can also promote the nuclear uptake of large plasmid DNA and increase the transfection efficiency. 302,328,329 For researchers endeavoring to improve the nuclear uptake of DNA cargo with polymer-based vehicles, it would be helpful to understand what levels of nuclear uptake are typically achieved with standard PEI-based transfections. Using quantitative polymerase chain reaction measurements, Szoka et al detected as few as 75 and as many as 50 000 plasmid copies (<5% of the applied dose) in the nuclei of transfected cells but found that levels above 3000 plasmids/nuclei yielded marginal returns in transgene expression.…”
Section: Intracellular Barriersmentioning
confidence: 99%
“…299 Dexamethasone dilates the nuclear pores, which can also promote the nuclear uptake of large plasmid DNA and increase the transfection efficiency. 302,328,329 For researchers endeavoring to improve the nuclear uptake of DNA cargo with polymer-based vehicles, it would be helpful to understand what levels of nuclear uptake are typically achieved with standard PEI-based transfections. Using quantitative polymerase chain reaction measurements, Szoka et al detected as few as 75 and as many as 50 000 plasmid copies (<5% of the applied dose) in the nuclei of transfected cells but found that levels above 3000 plasmids/nuclei yielded marginal returns in transgene expression.…”
Section: Intracellular Barriersmentioning
confidence: 99%
“…No entanto, esta estratégia não tem se mostrado muito bem-sucedida em estudos clínicos, sendo um dos motivos alegados a falta de vetores seguros e eficientes para entregar genes exógenos terapêuticos às células alvos dos pacientes (Kay et al, 2001). A utilização de novos métodos para entrega celular de material genético exógeno possibilita o tratamento de diversas doenças adquiridas ou hereditárias, através do reparo ou substituição do gene defeituoso, resultando na modulação da expressão da proteína associada com a doença (Boyle et al, 2019;Tang et al, 2014).…”
Section: Sistemas Voltados Para Entregas De Genes E Manipulação Do Materials Genéticounclassified
“…Alguns trabalhos corroboram esses achados, uma vez que a CQ contribuiu para aumentar níveis de atividade de transfecção do polímero polietilenimina de baixo peso molecular (PLGE) (Deng et al, 2011). A CQ também foi utilizada para desestabilizar os endossomos, resultando em um aumento significativo da transfecção de plasmídeos grandes, o que pode levar a um melhor desenvolvimento de veículos não virais para edição de gene CRISPR-Cas9 ex vivo (Boyle et al, 2019).…”
Section: Sistemas Voltados Para Entregas De Genes E Manipulação Do Materials Genéticounclassified
“…Corticosteroid Dexamethasone can dilate the nuclear pores 70 . Reineke's group investigated the effect of dexamethasone on nuclear permeability of induced pluripotent stem cells (iPSCs) and primary human dermal fibroblasts (HDFs) 71 . They utilized dexamethasone to pretreat the cells in cultures before transfection and got a 16‐fold increase in transfection efficiency compared to carrier alone for the large pDNA transfection.…”
Section: Polymeric Gene Delivery Enhancersmentioning
confidence: 99%